LOCUS OF CONTROL THEORY IN TREATING TOURIST BEHAVIOR: THE THEORY ROOTS AND RESEARCH DIRECTION IN DESTINATION BRANDING FIELD - Mohamed Ahmed GOUDA; Amany E. SALEM; Mostafa A. ABDELMOATY; Sanaa MABROUK; Mohamed Y. HELAL; Amal Salah Darder MOHAMED; Hala Ahmed Dafaalla KARAR; Elham Farouq Ali MOHAMMED; Khaled GHAZY (Geo Journal of Tourism and Geosites, 2023)
We aim to shed light on this issue by reviewing the roots and development of the locus of control theory. Moreover, we will introduce how we can use this development, in theory, to provide a new research direction in the tourism service field. A theory-based review was conducted to investigate the locus of control theory roots and its potential implications in the tourism industry using the Australian Business Deans Council (ABDC) list to explore the current literature. We followed the PRISMA methodology to collect the data from the Scopus database as well as Google Scholar and ResearchGate. The study found that the locus of control theory has its roots in social psychology and has been developed over the years to explain individual differences in behavior and decision-making. In the tourism service field, we found that understanding the locus of control can help service providers tailor their services to meet the needs and expectations of different types of tourists. This will contribute to attribution literature in psychological aspects and tourism literature with a deep understanding of how tourists behave and interpret differently.